Resolving uncertainties in predictive equations for urban tree crown characteristics of the southeastern United States: Local and general equations for common and widespread species (2016)
Urban forest research and management requires improved methods for quantifying ecosystem structure and function. Regional equations for urban tree crown width and height can accordingly improve predictions of urban tree structure. Using a large regional dataset with 12 locations in the southeastern US, we developed diameter-based equations for 97 urban tree species. Whereas previously published urban equations have almost exclusively been developed with one location on public or commercial land, our data included both public and private land uses. For 5 widespread, common urban tree species (Acer rubrum, Cornus florida, Pinus taeda, Quercus nigra and Lagerstroemia spp.), we also assessed the inclusion of additional variables such as crown light exposure, land cover, basal area, and location. Overall, height and crown width models were improved when including additional predictors, although competition and location effects varied by species. Study city was a significant predictor of tree height in all species except C. florida, and a significant predictor of crown width for all species except C. florida and Q. nigra. This indicates that anthropogenically-influenced variation among cities can lead to significant differences in both tree form and structure and that future model development should utilize data encompassing multiple cities. Our predictive equations for urban tree crown characteristics provide an improved method for planning, management, and estimating the provision of ecosystem services to improve quality of life in cities. © 2016 Elsevier GmbH